(untitled) (Research, Society and Development, 2022)
With the population’s interest in species of the Orchidaceae family, there is a high rate of predatory capture, which can threaten the species in its natural habitat. In view of the above, this work aimed to map, identify and characterize the environment/habitat of the orchid population found in a fragment of Atlantic Forest with transition to the Cerrado at IFSEMG - Campus Barbacena, through a systematic floristic survey by plots. distributed in the area around the longitudinal transects. 10 transects were laid along the path, within the fragment, with a distance of 150 m between each one. There were 3 plots in each transect, each measuring 15 m2 (3x5 m) and separated by 5 m, totaling a sample area of ​​0.045 ha. The number of individuals in each plot, the diversity of genera and the relationship between the density of individuals and environmental factors, such as altitude, luminosity and distance from the trail, were evaluated. The study found 6 genera: Campylocentrum, Capanemia, Encyclia, Epidendrum, Oncidium and Polystachya, with the Oncidium genus having the highest density. The plots further away from the trail had a greater number of individuals. As for luminosity, higher density of orchids in the plot. The same goes for the brightness factor. Through the results, it is concluded that the orchids of the genera found in the fragment were registered in a greater number of individuals in the habitats of greater luminosity and height.